Small things wide horizons : studies in honour of Birgitta Hårdh - Larsson, Lars; Ekengren, Fredrik; Helgesson, Bertil; Söderberg, Bengt, 1956-; Hårdh, Birgitta, 1945- (Archaeopress Publishing Ltd, 2015)
This publication honours Birgitta Hårdh on her 70th birthday. Birgitta Hårdh is one of the leading experts on European Viking Age, engaged in diverse research projects, and also a vital collaborator in various networks specializing in the period. Through time, Birgitta has extended her research to comprise other periods of the Iron Age. A feature common to all Birgitta Hårdh's research is that she has been able, through analysis of a body of finds, to broaden the perspective, not least geographically through her profound knowledge of phenomena in Northern Europe and indeed all of Europe.